Understanding nature ecology for a new generation - Weber, Louise M. (CRC Press, 2023)
Understanding Nature is a new kind of ecology textbook: a straight-forward resource that teaches natural history and ecological content, and a way to instruct students that will nurture both Earth and self. While meeting the textbook guidelines set forth by the Ecological Society of America, Understanding Nature has a unique ecotherapy theme, using a historical framework to teach ecological theory to undergraduates. This textbook presents all the core information without being unnecessarily wordy or lengthy, using simple, relatable language and discussing ecology in ways that any student can apply in real life. Uniquely, it is also a manual on how to improve one's relationship with the Earth. This is accomplished through coverage of natural history, ecology, and applications, together with suggested field activities that start each chapter and thinking questions that end each chapter. The book includes traditional ecological knowledge as well as the history of scientific ecological knowledge. Understanding Nature teaches theory and applications that will heal the Earth. It also teaches long-term sustainability practices for one's psyche. Professor Louise Weber is both an ecologist and a certified ecopsychologist, challenging ecology instructors to rethink what and how they teach about nature. Her book bridges the gap between students taking ecology to become ecologists and those taking ecology as a requirement, who will use the knowledge to become informed citizens"--